(untitled) (Medico Legal Update, 2020)
Background/Objectives: Sleep function affects human health,Recently, studies on various variables affecting mental health management and cognitive function of elderly people are being actively conducted due to the increase of elderly population. The purpose of this study was to investigate the correlation between cognitive function and quality of sleep in the elderly. Method/Statistical Analysis: The participation was 33 normal elders over 65-year-old. Cognition function was evaluated with the Montreal Cognitive Assessment (MoCA), and quality of sleep was evaluated with sleep Scale A. The data were then analyzed for frequency and correlation by using statistical software (SPSS 21.0). Findings: The average age of the study subjects was 82.4 years. The average MoCA score was 17.1±3.8 and sleep scale A score was 29.6±8.9. The results of MoCA and sleep scale A showed a positive correlation(r = .417, p<.05). Improvements/Applications: The results of the study show that the lower the quality of sleep in the elderly, the lower the cognitive function. The results of this study will discuss whether sleep quality can be used to predict mental health in older adults.